Sengketa Tanah Akibat Pendirian Gedung di Atas Tanah Hak Guna Bangunan : Delik-Delik di Luar KUHP No. 2160 K/Pdt/2017 - Azzarah Shifana Aliq Putrie; Hanuring Ayu Ardhani Putri (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines the legal protection provided to holders of Building Use Rights (HGB) on land under Management Rights (HPL) as interpreted in Supreme Court Decision No. 2160 K/Pdt/2017. The research aims to understand how civil law is applied to ensure legal certainty for HGB holders on HPL land and to strengthen insight into civil law principles used in resolving land-rights disputes. In the juridical context, land refers to the earth’s surface, while land rights are defined as authority over a specific, limited portion of that surface. Legal certainty, based on written regulations implementing the Basic Agrarian Law No. 5 of 1960, provides clarity regarding the rights and obligations of parties who own or control land. The study was conducted at the Sragen Police Resort using documentation methods—reviewing legal texts, literature, and supporting materials—along with field data obtained through interviews with relevant officers and individuals familiar with the case. The findings show that the Judex Facti of the West Java High Court made an error by declaring that no new issues required examination without giving adequate legal reasoning. The court also failed to address the objections submitted by the appellant, violating Article 50 paragraph (1) of Law No. 48 of 2009 on Judicial Power. Consequently, the Supreme Court annulled the previous decision, clarifying the legal consequences and strengthening the interpretation of HGB status on HPL land.